Revolutionizing Concrete Quality Through Global Innovations: Merevolusi Kualitas Beton Melalui Inovasi Global - Sidhi Cahyana, Atikha; Romadhon, Ilham Fatwa; Jakaria, Ribangun Bamban; Wahyuni, Hana Catur (Indonesian Journal of Innovation Studies, 2024)
The concrete industry, known for producing various concrete products, faces quality challenges evidenced by a 20% defect rate in concrete type G5. SP. 100. 100. 120. 10 MF from August 2022 to January 2023. This study aims to identify the root causes of defects to aid companies in enhancing product quality. Employing qualitative and quantitative methods, including the Seven Tools and Root Cause Analysis (RCA), the research uncovered predominant defects: 681 porous, 312 chipped, 196 cracked, 132 bug hole, 93 shrinkage, 85 lumpy, and 72 other defects. Human, material, machine, method, environmental factors contributed to these defects. Corrective actions were recommended to mitigate defects. The study's limitations include its focus solely on concrete type G5. SP. 100. 100. 120. 10 MF, suggesting future research should encompass all concrete types to provide comprehensive insights for the industry. Highlight: Automotive innovation drives rapid progress in technology and productivity. Consumers prioritize quality and quantity in vehicle selection. Modified racing rollers enhance motorcycle performance, boosting power and torque. Keywoard: Innovation, Technology, Automotive, Development, Productivity